Implementation of School Culture Based on Pancasila Values at the Elementary School Level in Muara Tiga District, Pidie Regency - Hendriani Hendriani; Najmuddin Najmuddin; Siraj Siraj (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the leadership of elementary school principals, teachers’ behavior, and obstacles in applying the practical values of Pancasila deliberative at the elementary school level in Muara Tiga District, Pidie Regency. A qualitative descriptive approach was employed, with data collected from principals and teachers through observations, interviews, and documentation. Data analysis followed a structured process of reduction, presentation, and conclusion drawing. The results indicate that principals foster participatory culture, act as facilitators and mediators, make collaborative decisions, communicate effectively, serve as role models, encourage teacher involvement, and organize deliberations. Teachers implement deliberative Pancasila values by facilitating learning and providing fair and transparent assessments. Obstacles include students’ limited understanding of deliberation, insufficient teacher training, and a school culture that is not fully supportive. In conclusion, effective application of deliberative Pancasila values requires supportive leadership, teacher competence, and a conducive school culture